Don’t cut your marketing budget in a recession - KUMAR, Nirmalya (Institutional Knowledge at Singapore Management University, 2020)
Duplicate record, see full text at https://ink.library.smu.edu.sg/lkcsb_research/6592/. Companies tend to cut marketing in a recession. But firms that maintain their marketing spend while reallocating it to suit the context – be it in product developing, advertising and communication, or pricing – typically fare better than firms that cut their marketing investment.